Firm Performance, Participation in Global Value Chains and Service Inputs : Evidence from India - Manghnani, Ruchita (World Bank, Washington, DC, 2021)
This paper explores the relationship between the use of service inputs, participation in global value chains, and firm productivity. Services play the role of both an intermediate input in production and a coordinator. Using a detailed Indian firm-level data set from 1990–2017, the paper estimates the productivity premium associated with varying depths of global value chain integration and different intensities and types of services used in the production. The study finds that firms in global value chains have a productivity premium between 13 and 22 percent relative to domestic firms, with some variation based on the depth of global value chain integration and the sector to which the firm belongs. Both the type of service inputs used (composition of services) and the origin of services (whether sourced domestically or from abroad) matter for firm performance. While higher aggregate service input use (as captured by the share of expenditure on service inputs) is not necessarily associated with an increase in productivity, increased use of complex services and information technology services is associated with higher productivity. The use of imported services is associated with higher productivity. Moreover, firms that are more deeply integrated in global value chains benefit more from importing services.